Structural, electrical and photoresponse properties of si-based diode with organic interfacial layer containing novel cyclotriphosphazene compound - Tataroğlu, A.; Özen, Furkan; Koran, Kenan; Dere, Ayşegül; Görgülü, Ahmet Orhan; Al-senany, Norah; Al-ghamdi, Ahmed; Farooq, W. A.; Yakuphanoğlu, Fahrettin (My University, 2017)
The electrical and photoresponse properties of an Al/p-Si/organic layer/Al diode were investigated. The organic layer containing novel 2,2-bis[spiro(7,8-dioxy- 4-methylcoumarin)]-4,4,6,6-bis[spiro(2’,2”-dioxy-1’,1”- biphenylyl)]cyclotriphosphazene compound was coated by the drop casting method on p-Si having ohmic contact. The structural characterization of the novel cyclotriphosphazene compound was confirmed by using 1H, 13C and 31P-NMR, elemental analysis and FTIR spectroscopic techniques. The diode exhibits a photoconducting and photodiode behavior under solar light illumination. The electrical parameters such as ideality factor, barrier height and series resistance of the diode were determined from I-V characteristics. It is seen that the photocurrent of the diode under illumination is higher than the dark current. Also, the frequency dependence of capacitance (C) and conductance (G) was explained on the basis of interface states. It is evaluated that the hybrid photodiode can be used as a photosensor in organic photodetector applications.
Yeni siklotrifosfazen bileşiği içeren organik arayüz katmanlı si-tabanlı diyodun yapısal, elektriksel ve fotoresponse özellikleri
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Organic photovoltaic diode; Cyclotriphosphazene; Coumarin-phosphazene